Tolstoy and His Problems : Views from the Twenty-First Century - Medzhibovskaya, Inessa, 1964- (Studies in Russian literature and theory., 2018)
Assessing the relevance of Tolstoy's thought and teachings for the current day, Tolstoy and His Problems: Views from the Twenty-First Century is a collection of essays by a group of Tolstoy specialists who are leading scholars in the humanities and social sciences. In the broadest sense--with essays on a variety of issues that occupied Tolstoy, such as nihilism, mysticism, social theory, religion, Judaism, education, opera, and Shakespeare--the volume offers a fresh evaluation of Tolstoy's program to reform the ways we live, work, commune with nature and art, practice spirituality, exchange ideas and knowledge, become educated, and speak and think about history and social change.